Laser Induced Fluorescence Spectroscopy of Decamethylrhenocene ( - C5 Me5)2 Re in Supersonic Jet - Saleh, Harith J. (Iraqi Journal of Laser, 2019)
In this paper we report the use of supersonic jet laser induced fluorescence (LIF) spectroscopy to facilitate the study of the spectra of some organometallic sandwich compounds particularly the metallocenes. The charge-transfer processes within these compounds, especially ligand to metal charge transfer within decamethylrhenocene ( - C5 Me5)2 Re were of particular interest. The spectrum shows a high degree of structures, indicating that there are several levels populated and these molecules are able to undergo many possible transitions